Synthesis of Icariin-Zinc and its Protective Effect on Exercise Fatigue and Reproductive System Related Glands in Male Rats - Zhang, Juntao; Zhang, Chao; Liu, Aifeng; Ji, Qiang; Ren, Lixia; Ma, Chuanrui; Zhang, Hengyu; Wu, Chaochao; Zhang, Donglin; Shang, Man; He, Feng (Frontiers in Pharmacology, 2021)
Background: Icariin, a traditional Chinese medicine, plays a protective role in the treatment of exercise fatigue. Zinc, a trace element, plays an important role in the reproductive system. Therefore, we aimed to synthesize an Icariin-Zinc complex (by chemical means) and verify its protective effect on exercise fatigue and the reproductive system using animal experiments. Methods: The icariin-zinc complex was prepared by the reaction of icariin carbonyl and zinc ions (molar ratio 1:3). The molecular formula and structural formula of the complex were identified and tested. Fifty-six rats selected by swimming training were randomly divided into six groups: static control, exercise control, icariin, gluconate zinc (G-Zn group), icariin glucose zinc and icariin-zinc exercise ( low, high dose/L-E group, H-E group) groups. These groups respectively received the following doses: 1 ml/100 g, daily gavage with NS (for the first two groups), 45 mg/kg icariin, 110 mg/kg Gluconate Zinc, Icariin glucose zinc (45 mg/kg Icariin and 110 mg/kg Gluconate Zinc), 60 mg/kg icariin zinc and 180 mg/kg icariin zinc. After 3 weeks of gavage, we conducted 6 weeks of exhaustive swimming training. Test indices such as exhaustive swimming time of rats and body weight were evaluated after the last training exercise. The seminal vesicles, testes, and prostate gland were weighed, and their indices were calculated. The levels of testosterone (in the plasma) and glycogen (in the liver and muscle homogenates) were also evaluated using ELISA. Results: Compared with the static control group, the exhaustive swimming time of the rats in each group was prolonged. Compared with the other groups, the exhaustive swimming time of the L-E and H-E groups was significantly longer (p < 0.01); the Icariin-Zinc complex significantly increased the exhaustive swimming time of the rats. Compared with the static control group, the plasma testosterone content of the L-E and H-E groups increased significantly (p < 0.05). Compared with the exercise control group and G-Zn group, the plasma testosterone content of the H-E group also increased significantly (p < 0.01). The Icariin-Zinc complex significantly increased the serum levels of testosterone in rats. Compared with the control group, the muscle glycogen reserves of each group decreased, indicating that the muscle glycogen reserves of the rats decreased after swimming. Compared with other groups, the Icariin-Zinc complex can reduce the level of glycogen in the muscles, indicating that it can increase the utilization efficiency of glycogen in muscles. Compared with the static control and exercise control groups, the testicular weight of rats in the administration groups increased slightly. The Icariin-Zinc complex increased the testicular weight, indicating that the function of the reproductive system was improved to some extent. Conclusion: Icariin-Zinc can significantly prolong the exhaustive swimming time, improve exercise ability, and increase the plasma testosterone level (which is beneficial for improving the reproductive ability of male rats). Moreover, the beneficial effect of Icariin-Zinc on the glycogen content, testis index, and other reproductive system glands is dose-dependent.